Potret Ketertindasan terhadap Perempuan Bali dalam Novel Tarian Bumi - Aprilia, Pascalin Dwi (Educatio Christi, 2024)
This article discusses an issue of discrimination against Balinese women depicted in a novel entitled "Tarian Bumi". The issue of discriminatory treatment of women is no longer an issue that can be underestimated and underestimated. This research work was carried out using qualitative research methods, literature study approaches and data analysis. From the research work carried out, it was found that the issue of discriminatory treatment depicted in the novel “Tarian Bumi” was caused by the culture that society lives today. The results of the analysis conducted in this article are compared with the stories from the Bible Genesis 16:1-16 and Genesis 21:8-21 that speak of Hagar. The oppression of women is not a light issue and must be the attention of various levels of society.